We think you are located in South Africa. Is this correct?

Double Angle Identities

4.3 Double angle identities (EMCGD)

Derivation of \(\sin2\alpha\) (EMCGF)

We have shown that \(\sin\left(\alpha +\beta \right)=\sin\alpha\cos \beta +\cos\alpha\sin \beta\). If we let \(\alpha =\beta\), then we can write the formula as:

\begin{align*} \sin \left(2\alpha \right) &= \sin\left(\alpha +\alpha \right) \\ & = \sin \alpha\cos \alpha +\cos\alpha\sin \alpha \\ \therefore \sin 2\alpha & = 2\sin\alpha\cos \alpha \end{align*}

Derivation of \(\cos2\alpha\) (EMCGG)

Similarly, we know that \(\cos\left(\alpha +\beta \right)=\cos\alpha\cos \beta -\sin\alpha\sin \beta\). If we let \(\alpha =\beta\), then we have:

\begin{align*} \cos \left(2\alpha \right) &=\cos\left(\alpha +\alpha \right) \\ & = \cos \alpha\cos \alpha -\sin\alpha\sin \alpha \\ \therefore \cos 2\alpha & = \cos^{2}\alpha -\sin^{2}\alpha \end{align*}

Using the square identity, \(\sin^{2} \alpha + \cos^{2}\alpha = 1\), we can also derive the following formulae:

\begin{align*} \cos 2\alpha & = \cos^{2}\alpha -\sin^{2}\alpha \\ & = \left( 1 - \sin^{2}\alpha \right) - \sin^{2}\alpha \\ \therefore \cos 2\alpha & = 1 - 2 \sin^{2}\alpha \end{align*}

And

\begin{align*} \cos 2\alpha & = \cos^{2}\alpha -\sin^{2}\alpha \\ & = \cos^{2}\alpha - \left( 1 - \cos^{2}\alpha \right) \\ & = \cos^{2}\alpha - 1 + \cos^{2}\alpha \\ \therefore \cos 2\alpha & = 2 \cos^{2}\alpha - 1 \end{align*}

Double angle formulae

  • \(\sin 2\alpha = 2\sin\alpha\cos \alpha\)
  • \(\cos 2\alpha = \cos^{2}\alpha -\sin^{2}\alpha\)
  • \(\cos 2\alpha = 1 - 2 \sin^{2}\alpha\)
  • \(\cos 2\alpha = 2 \cos^{2}\alpha - 1\)

Worked example 7: Double angle identities

If \(\alpha\) is an acute angle and \(\sin \alpha = \text{0,6}\), determine the value of \(\sin 2 \alpha\) without using a calculator.

Draw a sketch

We convert \(\text{0,6}\) to a fraction so that we can use the ratio to represent the sides of a triangle.

\begin{align*} \sin \alpha &= \text{0,6} \\ &= \frac{6}{10} \end{align*}4974a23802f7c78d4f17c5ac6926dfce.png

Use the double angle formula to determine the value of \(\sin 2 \alpha\)

\begin{align*} \sin 2 \alpha &= 2 \sin \alpha \cos \alpha \\ &= 2 \left( \frac{6}{10} \right) \left( \frac{8}{10} \right) \\ &= \frac{96}{100} \\ &= \text{0,96} \end{align*}

Write the final answer

\[\sin 2 \alpha = \text{0,96}\]

Check the answer using a calculator:

\begin{align*} \sin \alpha &= \text{0,6} \\ \therefore \alpha &\approx \text{36,87} ° \\ 2 \alpha &\approx \text{73,74} ° \\ \therefore \sin \left( \text{73,74} ° \right) &\approx \text{0,96} \end{align*}

Worked example 8: Double angle identities

Prove that \(\frac{\sin\theta +\sin2\theta }{1 + \cos\theta +\cos2\theta } = \tan\theta\).

For which values of \(\theta\) is the identity not valid?

Consider the given expressions

The right-hand side (RHS) of the identity cannot be simplified, so we simplify the left-hand side (LHS). We also notice that the trigonometric function on the RHS does not have a \(2\theta\) dependence, therefore we will need to use the double angle formulae to simplify \(\sin2\theta\) and \(\cos2\theta\) on the LHS.

Prove the left-hand side equals the right-hand side

\begin{align*} \text{LHS}& = \frac{\sin\theta + 2\sin\theta \cos\theta }{1+\cos\theta +\left(2{\cos}^{2}\theta -1\right)} \\ & = \frac{\sin\theta \left(1+2\cos\theta \right)}{\cos\theta \left(1+2\cos\theta \right)} \qquad \text{(factorise)} \\ & = \frac{\sin\theta }{\cos\theta } \\ & = \tan \theta \\ & = \text{RHS} \end{align*}

Identify restricted values of \(\theta\)

We know that \(\tan \theta\) is undefined for \(\theta = \text{90} ° + k \cdot \text{180} °, k \in \mathbb{Z}\).

Note that division by zero on the LHS is not allowed, so the identity will also be undefined for:

\begin{align*} 1 + \cos\theta +\cos2\theta & = 0 \\ \cos\theta \left( 1 + 2\cos\theta \right) & = 0 \\ \therefore \cos \theta = 0 &\text{ or } 1 + 2\cos\theta = 0 \\ & \\ \text{For } \cos \theta = 0, \quad \theta &= \text{90} ° + k \cdot \text{180} ° \\ & \\ \text{For } 1 + 2 \cos \theta = 0, \quad \cos \theta &= - \frac{1}{2} \\ \therefore \theta &= \text{120} ° + k \cdot \text{360} ° \\ \text{or } \theta &= \text{240} ° + k \cdot \text{360} ° \end{align*}

for \(k \in \mathbb{Z}\).

Practise now to improve your marks

You can do it! Let us help you to study smarter to achieve your goals. Siyavula Practice guides you at your own pace when you do questions online.

Sign up to improve your marks

Double angle identities

Exercise 4.3

Given \(5 \cos \theta = -3\) and \(\theta < \text{180} °\). Determine the value of the following, without a calculator:

\(\cos 2 \theta\)

Draw a sketch:

58741489b87a568044fce5c12baad72a.png
\(\sin \left( \text{180} ° - 2 \theta \right)\)
\begin{align*} \sin \left( \text{180} ° - 2 \theta \right) &= \sin 2 \theta \\ &= 2 \sin \theta \cos \theta \\ &= 2 \left( \frac{4}{5} \right) \left( - \frac{3}{5} \right) \\ &= - \frac{24}{25} \end{align*}
\(\tan 2 \theta\)
\begin{align*} \tan 2 \theta &= \frac{\sin 2 \theta}{\cos 2 \theta} \\ &= - \frac{24}{25} \times \left( - \frac{25}{7} \right) \\ &= \frac{24}{7} \end{align*}

Given \(\cos \text{40} ° = t\), determine (without a calculator):

\(\cos \text{140} °\)
\begin{align*} \cos \text{140} ° &= \cos \left( \text{180} ° - \text{40} ° \right) \\ &= - \cos \text{40} ° \\ &= - t \end{align*}
\(\sin \text{40} °\)
\begin{align*} \sin \text{40} ° &= \sqrt{1 - \cos^{2} \text{40} ° } \\ &= \sqrt{1 - t^{2}} \end{align*}
\(\sin \text{50} °\)
\begin{align*} \sin \text{50} ° &= \sin \left( \text{90} ° - \text{50} ° \right) \\ &= \cos \text{40} ° \\ &= t \end{align*}
\(\cos \text{80} °\)
\begin{align*} \cos \text{80} ° &= \cos 2 \left( \text{40} ° \right) \\ &= 2 \cos^{2} \text{40} ° - 1 \\ &= 2t^{2} - 1 \end{align*}
\(\cos \text{860} °\)
\begin{align*} \cos \text{860} ° &= \cos \left[2( \text{360} °) + \text{140} ° \right] \\ &= \cos \text{140} ° \\ &= \cos ( \text{180} ° - \text{40} °) \\ &= - \cos \text{40} ° \\ &= -t \end{align*}
\(\cos ( -\text{1 160} °)\)
\begin{align*} \cos (- \text{1 160} °) &= \cos \text{1 160} ° \\ &= \cos \left( 3( \text{360} °) + \text{80} ° \right) \\ &= \cos ( \text{80} °) \\ &= \cos 2( \text{40} °) \\ &= 2 \cos^{2} \text{40} ° - 1 \\ &= 2 t^{2} - 1 \end{align*}
Prove the identity: \(\frac{1}{\sin 2 A} - \frac{1}{\tan 2A} = \tan A\)
\begin{align*} \text{LHS} &= \frac{1}{\sin 2 A} - \frac{1}{\tan 2A} \\ &= \frac{1}{\sin 2 A} - \frac{\cos 2A}{\sin 2A} \\ &= \frac{1 - \left( 1 - 2 \sin^{2}A \right)}{\sin 2 A} \\ &= \frac{2 \sin^{2}A}{2 \sin A \cos A} \\ &= \frac{\sin A}{\cos A} \\ &= \tan A \\ &= \text{RHS} \end{align*}

Restrictions:

\begin{align*} \sin 2 A &\ne 0 \\ \therefore 2A &\ne \text{0} ° + k \cdot \text{180} ° \\ \therefore A &\ne \text{0} ° + k \cdot \text{90} °, \quad k \in \mathbb{Z} \\ \text{And } \tan 2 A &\ne 0 \\ \therefore 2A &\ne \text{90} ° + k \cdot \text{180} ° \\ \therefore A &\ne \text{45} ° + k \cdot \text{90} °, \quad k \in \mathbb{Z} \\ \text{And for } \tan A &: \\ A &\ne \text{90} ° + k \cdot \text{180} °, \quad k \in \mathbb{Z} \end{align*}
Hence, solve the equation \(\frac{1}{\sin 2 A} - \frac{1}{\tan 2A} = \text{0,75}\) for \(\text{0} ° < A < \text{360} °\).
\begin{align*} \frac{1}{\sin 2 A} - \frac{1}{\tan 2A} &= \text{0,75} \\ \therefore \tan A &= \text{0,75} \\ \therefore A &= \text{36,87} ° \\ \text{ or } A &= \text{180} ° + \text{36,87} °\\ &= \text{216,87} ° \end{align*}

Without using a calculator, find the value of the following:

\(\sin \text{22,5} °\)
\begin{align*} 2 \times \text{22,5} ° &= \text{45} ° \\ \cos 2 \theta &= 1 - 2 \sin^{2} \theta \\ \cos \text{45} ° &= 1 - 2 \sin^{2} \left( \text{22,5} ° \right) \\ \frac{1}{\sqrt{2}} &= 1 - 2 \sin^{2} \left( \text{22,5} ° \right) \\ \frac{1}{\sqrt{2}} - 1 &= - 2 \sin^{2} \left( \text{22,5} ° \right) \\ \frac{1 - \sqrt{2}}{\sqrt{2}} &= - 2 \sin^{2} \left( \text{22,5} ° \right) \\ \frac{1 - \sqrt{2}}{-2\sqrt{2}} &= \sin^{2} \left( \text{22,5} ° \right) \\ \frac{ \sqrt{2} - 1}{2\sqrt{2}} &= \sin^{2} \left( \text{22,5} ° \right) \\ \therefore \sqrt{ \frac{ \sqrt{2} - 1}{2\sqrt{2}} } &= \sin \text{22,5} ° \\ \sqrt{ \frac{ \sqrt{2} - 1}{2\sqrt{2}} \times \frac{\sqrt{2}}{\sqrt{2}}} &= \sin \text{22,5} ° \\ \sqrt{ \frac{ 2 - \sqrt{2} }{4} } &= \sin \text{22,5} ° \end{align*}

Check the answer using a calculator.

\(\cos \text{67,5} °\)
\begin{align*} \cos \text{67,5} ° &= \cos \left( \text{90} ° - \text{22,5} ° \right) \\ &= \sin \left( \text{22,5} ° \right) \\ &= \sqrt{ \frac{ 2 - \sqrt{2} }{4} } \end{align*}

Check the answer using a calculator.

Prove the identity: \(\tan 2 x + \frac{1}{\cos 2 x} = \frac{\sin x + \cos x }{\cos x - \sin x }\)
\begin{align*} \text{LHS} &= \tan 2x + \frac{1}{\cos 2x} \\ &= \frac{\sin 2x}{\cos 2x} + \frac{1}{\cos 2x} \\ &= \frac{\sin 2x + 1}{\cos 2x} \\ &= \frac{2 \sin x \cos x + \cos^{2}x + \sin^{2}x}{\cos^{2}x - \sin^{2}x} \\ &= \frac{ \left( \cos x + \sin x \right)^{2}}{\left( \cos x - \sin x \right)\left( \cos x + \sin x \right) } \\ &= \frac{ \cos x + \sin x }{ \cos x - \sin x } \\ &= \text{RHS} \end{align*}

Restrictions:

\begin{align*} \cos 2 x &\ne 0 \\ \therefore 2x &\ne \text{90} ° + k \cdot \text{180} ° \\ \therefore x &\ne \text{45} ° + k \cdot \text{90} °, \quad k \in \mathbb{Z} \\ \text{And } \cos x &\ne \sin x \\ \therefore x &\ne \text{45} ° + k \cdot \text{180} °, \quad k \in \mathbb{Z} \\ \text{And for } & \tan 2 x \\ \therefore 2x &\ne \text{90} ° + k \cdot \text{180} ° \\ \therefore x &\ne \text{45} ° + k \cdot \text{90} °, \quad k \in \mathbb{Z} \end{align*}
Explain why the identity is undefined for \(x = \text{45} °\)

Consider the denominator on the LHS:

\begin{align*} \cos 2x &= \cos 2 \left( \text{45} ° \right) \\ &= \cos \text{90} ° \\ &= 0 \end{align*}

Consider the denominator on the RHS:

\begin{align*} \cos \text{45} ° &= \sin \text{45} ° \\ \therefore \cos \text{45} ° - \sin \text{45} ° &= 0 \end{align*}

Therefore, the identity will be undefined because division by zero is not permitted.